Sample Preparation for Translucent and Scanning Electron Microscopy: New Leica Microsystems Coaters - Niemova, S.V. (Science and Innovation, 2024)
The research deals with new Leica Microsystems desktop coaters used for application of conductive layers in vacuum. Their technical specifications and scope of application have been described.